2023
DOI: 10.6065/apem.2244196.098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of once-weekly dulaglutide on juvenile type 2 diabetes mellitus and obesity in Korea: a pilot study

Abstract: To investigate the effects and side effects of once weekly dulaglutide treatment for type 2 diabetes mellitus (T2DM) in patients under the age of 18 years in Korea. Methods:From the Eulji University Hospital database, we identified all patients under the age of 18 years diagnosed with T2DM and treated with dulaglutide from January 1, 2017 to July 31, 2022. Results:We identified five patients under the age of 18 years treated with dulaglutide for T2DM management. Their mean (SD) age was 16.6 (0.5) years. Four (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…An investigation in Korea assessed the efficacy and side effects of once-weekly dulaglutide in treating YODM. The results indicated excellent glycemic control with once-weekly dulaglutide for YODM, with no significant side effects ( 146 ). However, other studies found additional side effects of GLP-1 agonists, including vomiting, diarrhea, abdominal pain, hypoglycemia, elevated transaminases, and pancreatitis ( 147 ).…”
Section: Comprehensive Management Strategies For Yodm From the Perspe...mentioning
confidence: 99%
“…An investigation in Korea assessed the efficacy and side effects of once-weekly dulaglutide in treating YODM. The results indicated excellent glycemic control with once-weekly dulaglutide for YODM, with no significant side effects ( 146 ). However, other studies found additional side effects of GLP-1 agonists, including vomiting, diarrhea, abdominal pain, hypoglycemia, elevated transaminases, and pancreatitis ( 147 ).…”
Section: Comprehensive Management Strategies For Yodm From the Perspe...mentioning
confidence: 99%
“…The current study is the first report to determines the effects and side effects of once-weekly dulaglutide in juvenile T2DM under the age of 18 years in Korea [ 12 ]. Despite the small number, this study also indicated that the use of dulaglutide may be another potential therapeutic, safe option in young patients with poorly controlled T2DM.…”
mentioning
confidence: 99%